Boundedness and global solvability for a chemotaxis-haptotaxis model with p-Laplacian diffusion - Changchun Liu (Electronic Journal of Differential Equations, 2020)
We consider a chemotaxis-haptotaxis system with $p$-Laplacian diffusion in three dimensional bounded domains. It is asserted that for any p>2, under the appropriate assumptions, the chemotaxis-haptotaxis system admits a global bounded weak solution if for initial data satisfies certain conditions.